Correlation assessment between working and academic performance - Nur Shahida Ab Fatah; Nur Ainna Ramli; Dian Darina Indah Daruis; Farhana Diana Deris; Noorsidi Aizuddin Mat Noor; Aslina Baharum (Winter and Spring 2021, 2021)
Working while studying is common, with at least half of all students taking a paid job at some point throughout their studies. By combining working and studying simultaneously will impact the academic performance of students. The main issues are the consequences of working while studying, which results in declining academic performance. This study aimed to identify possible reasons that cause students to work and study simultaneously, assess the correlation between work and academic performance, and determine the main barriers students face as they work and study. Using quantitative method, data was collected from 218 students from undergraduate and postgraduate, who have experienced study while working. Results show that most students agreed that working while studying correlates with academic performance. Furthermore, it is necessary to learn about the positive and negative effects of their efforts that distract them all this time. Having known all, these factors helped this study develop a good strategy for maintaining a better life while working and studying simultaneously.